Gospodarcze konsekwencje liberalizacji rynku gazu ziemnego w Niemczech - Winkler, Bartholomäus (Gospodarka w Praktyce i Teorii, 2012)
The article is about the liberalization of the gas market in Germany. It contains characteristics of main elements of the market and an assessment of the process of liberalization. There were also formulated recommendations for further research and suggestions for Poland, that is about to face challenges related to the implementation of European Union directives relating to the liberalization of the energy market.